Comparison of two methods for glucocorticoid evaluation in maned wolves - Vasconcellos,Angélica S (2011)
Analysis of faecal glucocorticoid metabolites provides a powerful noninvasive tool for monitoring adrenocortical activity in wild animals. However, differences regarding the metabolism and excretion of these substances make a validation for each species and sex investigated obligatory. Although maned wolves (Chrysocyon brachyurus) are the biggest canids in South America, their behaviour and physiology are poorly known and they are at risk in the wild. Two methods for measuring glucocorticoid metabolites in maned wolves were validated: a radio- and an enzyme immunoassay. An ACTH challenge was used to demonstrate that changes in adrenal function are reflected in faecal glucocorticoid metabolites. Our results suggest that both methods enable a reliable assessment of stress hormones in maned wolves avoiding short-term rises in glucocorticoid concentrations due to handling and restraint. These methods can be used as a valuable tool in studies of stress and conservation in this wild species.